Pengaruh Faktor Sosial Ekonomi terhadap Perkawinan Muslim di Indonesia - Fauzia Aqilla Fadhil; Ilmiawan Auwalin (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to find out what factors that affect a Muslim's decision to get married. This study uses the data from the Indonesian Family Life Survey (IFLS) with a quantitative approach using 83% of the sample population in Indonesia covering approximately 30,000 people taken in 13 of the 27 provinces in Indonesia. This study was analyzed using Linear Probability Model (LPM) regression, Logit regression and Probit regression. The data in this study were processed using STATA MP software. According to the results of data using three regression models, the factors that affect the decision of each individual in Indonesia in general to marry are gender, religion, age, education and occupation. The factors that affect each individual Muslim in Indonesia to make a decision to marry are gender, age, education and occupation. Then, for women in Indonesia in general, the factors that affect the decision to get married are religion, age, and occupation. Last but not least, for Muslim women, the factors that affect the decision to marry is age and occupation.Keywords: Socio-Economy, Muslim Marriage, Marital DecisionREFFERENCESBumpass, L. 1969. Age at Marriage as a Variable in Socio-Economic Differentials in Fertility.Demography, 6(1), 45.Hosmer, D. dan W S.Lemeshow. 2000. Applied Logistic Regression2nd Edition. New York: John Willey and SonsPerry, S. L. 2014. A Match Made in Heaven? Religion-Based Marriage Decisions, MaritalQuality, and the Moderating Effects ofSpouse’s Religious Commitment. Social Indicators ResearchSugiyono.2013.Metodelogi Penelitian Kuantitatif, Kualitatif Dan R&D. (Bandung: ALFABETA)Surjoamihardjo. 1962. Karya K.H. Dewantara, Bagian Pertama: Pendidikan . Jogjakarta: Madjelis Luhur Persatuan Taman Siswa.Wolfinger, Nick.2016.Replicating the Goldilocks Theory of Marriage and Divorce. USA : University of Utah.